The immediate impact of the first waves of the global COVID-19 pandemic on agricultural systems worldwide: Reflections on the COVID-19 special issue for agricultural systems. (August 2022) - Stephens, Emma; Timsina, Jagadish; Martin, Guillaume; van Wijk, Mark; Klerkx, Laurens; Reidsma, Pytrik; Snow, Val
Abstract: CONTEXT: In May 2020, approximately four months into the COVID-19 pandemic, the journal's editorial team realized there was an opportunity to collect information from a diverse range of agricultural systems on how the pandemic was playing out and affecting the functioning of agricultural systems worldwide. OBJECTIVE: The objective of the special issue was to rapidly collect information, analysis and perspectives from as many regions as possible on the initial impacts of the pandemic on global agricultural systems, The overall goal for the special issue was to develop a useful repository for this information as well as to use the journal's international reach to share this information with the agricultural systems research community and journal readership. METHODS: The editorial team put out a call for a special issue to capture the initial effects of the pandemic on the agricultural sector. We also recruited teams from eight global regions to write papers summarizing the impacts of the first waves of the pandemic in their area. RESULTS AND CONCLUSIONS: The work of the regional teams and the broader research community resulted in eight regional summary papers, as well as thirty targeted research articles. In these papers, we find that COVID-19 and global pandemic mitigation measures have had significant and sometimes unexpected impacts on our agricultural systems via shocks to agricultural labour markets, trade and value chains. And, given the high degree of overlap between low income populations and subsistence agricultural production in many regions, we also document significant shocks to food security for these populations, and the high potential for long term losses in terms of human, natural, institutional and economic capital. While we also documented instances of agricultural system resilience capacities, they were not universally accessible. We see particular need to shore up vulnerable agricultural systems and populations most negatively affected by the pandemic and to mitigate pandemic-related losses to preserve other agricultural systems policy objectives, such as improving food security, or addressing climate change. SIGNIFICANCE: Despite rapid development of vaccines, the pandemic continues to roll on as of the time of writing (early 2022). Only time will tell how the dynamics described in this Special Issue will play out in the coming years. Evidence of agricultural system resilience capacities provides some hopeful perspectives, but also highlights the need to boost these capacities across a wider cross section of agricultural systems and encourage agri-food systems transformation to prepare for more challenges ahead. Graphical abstract: Unlabelled Image Highlights: 8 regional summaries, 30 research papers on agricultural systems responses to the initial waves of the pandemic The Special Issue primarily highlights immediate impact of COVID-19 mitigation measures on agricultural systems Emerging impacts include widespread impacts on food security for vulnerable populations engaged in agriculture Additional impacts via disruptions to agricultural labour and trade, agricultural incomes and livelihoods Evidence of resilience capacities within many agricultural systems to the pandemic, but not universal